Microsoft Windows Vista unleashed - McFedries, Paul (Sams, 2008)
Microsoft℗ʼ Windows Vista<U+00CC><U+0081>⁴©<U+0098> Unleashed, Second Edition Paul McFedries Second Edition Includes coverage of Windows Vista Service Pack 1! Microsoft Windows Vista Unleashed, Second Edition, is a book for people, like you, who don't consider themselves to be "average users." It's a book for anyone who finds that doing things the official way is slower, less efficient, and less powerful because Windows Vista was designed from the ground up to avoid confusing novice users. The result is default settings that restrict flexibility, interminable wizards that turn 2-step tasks into 12-step sagas, and the hiding of powerful and useful programs behind layers of menus and dialog boxes. To unleash the potential of Windows Vista, you need a different approach that blows away Vista's novice features and scorns the standard way of doing things. This book goes beyond the standard-issue techniques sanctioned by Microsoft and parroted in other Windows Vista books. Instead, this book offers shortcuts for boosting your productivity, customizations for making Windows Vista work the way you do, workarounds for known Windows Vista problems, and warnings for avoiding Windows Vista pitfalls. Along the way, you'll learn about all kinds of insider details, undocumented features, powerful tools, and background facts that help put everything into perspective. Paul McFedries is the president of Logophilia Limited, a technical writing company. He has been working with computers for more than 30 years and has been using Microsoft Windows since version 1. Paul has written more than 50 books that have sold more than 3 million copies worldwide. Learn what's new in Windows Vista Service Pack 1 Customize Windows Vista startup Troubleshoot software and hardware problems Tune Windows Vista's performance Automate Windows Vista with powerful and flexible scripts Implement Internet security and privacy features Configure and administer a small network Get the most out of Control Panel, group policies, the Registry, Device Manager, and other powerful tools Set up a complete maintenance program to keep Windows Vista running smoothly Discover a complete list of Windows Vista shortcut keys, a detailed look at the Command Prompt, and a batch file primer Master the new desktop search engine and learn how to group, stack, and filter files Understand and work with Windows Vista's User Account Control security feature Get the most out of your Tablet PC Take advantage of new Internet features such as RSS feeds, multiple home pages, and tabbed browsing Category: Microsoft Operating Systems Covers: Microsoft Windows Vista User Level: Intermediate--Advanced.